β-Cyclodextrin conjugated bifunctional isocyanate linker polymer for enhanced removal of 2,4-dinitrophenol from environmental waters - Anne, J.M.; Boon, Yih Hui; Saad, Bahruddin; Miskam, Mazidatul Akmam; Yusoff, M.M.; Shahriman, Mohamad Shariff; Zain, Nur Nadhirah Mohamad; Lim, Vuanghao; Raoov, Muggundha (The Royal Society, 2018)
In this work, we reported the synthesis, characterization and adsorption study of two b-cyclodextrin (bCD) cross-linked polymers using aromatic linker 2,4-toluene diisocyanate (2,4-TDI) and aliphatic linker 1,6-hexamethylene diisocyanate (1,6-HDI) to form insoluble bCD-TDI and bCD-HDI. The adsorption of 2,4-dinitrophenol (DNP) on both polymers as an adsorbent was studied in batch adsorption experiments. Both polymers were well characterized using various tools that include Fourier transform infrared spectroscopy, thermogravimetric analysis, Brunauer-Emmett-Teller analysis and scanning electron microscopy, and the results obtained were compared with the native bCD. The adsorption isotherm of 2,4-DNP onto polymers was studied. It showed that the Freundlich isotherm is a better fit for bCD-TDI, while the Langmuir isotherm is a better fit for bCD-HMDI. The pseudo-second-order kinetic model represented the adsorption process for both of the polymers. The thermodynamic study showed that bCD-TDI polymer was more favourable towards 2,4-DNP when compared with bCD-HDI polymer. Under optimized conditions, both bCD polymers were successfully applied on various environmental water samples for the removal of 2,4-DNP. bCD-TDI polymer showed enhanced sorption capacity and higher removal efficiency (greater than 80%) than bCD-HDI (greater than 70%) towards 2,4-DNP. The mechanism involved was discussed, and the effects of cross-linkers on bCD open up new perspectives for the removal of toxic contaminants from a body of water.